An Industrial systems design on Walter Mart (E. Rodriguez Branch) - Olvidado, Ingrid; Po, Ronald; Tan, Katheryn; Tiongson, Ciselle (Diliman, Quezon City College of Engineering, 2003)
Walter Mart is a chain of stores with the "one stop-shop" concept. This concept intends to make everything available under one roof. The study focuses on the supermarket operations of Walter Mart E. Rodriguez, the company's first outlet. The store's processes and operations were analyzed. An analysis of the firm's strategy using SWOT analysis was also made. The company's mission and vision reflects its desire to be a leading provider of quality consumer goods through its retail outlets. It brings its stores closer to its customers by servicing communities that are erstwhile ignored by large retailing chains. It also has complementary stores that put into action the store's "one-stop-shop community center" concept. These complementary stores sell various products and services such as clothing, records, appliances, photo developing, and banking. An analysis of the company's strengths reveal that its strongest advantage over its competitors is its concept of having everything under one roof. The company also has a loyalty card program that suits very well with its main strength. However, more could be done to further enhance the program such as more aggressive marketing. Walter Mart's primary weakness is its relatively limited product selection and higher prices. It also has short operating hours (10 AM to 8 PM) considering that it is near schools, churches and hospitals. An increasing amount of allocation for personal expenditure, a slower inflation rate, and a positive population growth contribute as consistent opportunities for sales growth. The establishment of an in-house pharmacy (or as a complementary store) is also an opportunity due to the numerous hospitals surrounding the site. For businesses in general, the uncertainty brought about by the war in Iraq is always a looming threat. However, the main threat comes from Walter Mart's competitors such as Unimart and SM Centerpoint. The specific problems identified are the idle merchandisers, absence of an algorithm to properly schedule the cashiers, and the absence of properly documented quality control (QC) in the receiving operations. All of these are directly connected with the company's desire to increase customer service. The main recommendations of the study are the use of plastic pallets in the warehouse, implementation of work sampling for merchandisers, implementation of acceptance sampling techniques in receiving operations, and the application of a computational algorithm to schedule cashiers based on forecasts of arrivals. An implementation plan was provided in order to guide the company regarding the recommendations made. Among the areas for further study is the analysis of the cashier queue lines using a general distribution model since a Markovian model is not applicable. A feasibility study on the establishment of an in-house pharmacy (either Walter Mart-owned or as a complementary store) should be made. A future study can also be done on the feasibility of a store expansion.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Walter Mart (E. Rodriguez Branch); Supermarkets; System design